US Clinical Practice Experience with Eculizumab in Myasthenia Gravis: Acute Clinical Events and Healthcare Resource Utilization - Richard J. Nowak; Ali A. Habib; Andrew J. Klink; Srikanth Muppidi; Anju Parthan; S. Chloe Sader; Alexandrina Balanean; Ajeet Gajra; James F. Howard; ELEVATE Study Group (Adis, Springer Healthcare, 2024)
Abstract Background and Objective The terminal complement inhibitor eculizumab is approved in the USA for the treatment of patients with acetylcholine receptor antibody-positive generalized myasthenia gravis (MG). The ELEVATE study aimed to examine clinical-practice outcome data on eculizumab effectiveness in US adults with MG (generalized or ocular). This paper reports the findings on MG exacerbations and crises and associated healthcare resource utilization, and the use of rescue therapy. Methods A retrospective chart review was conducted of US adults with MG who initiated eculizumab. Outcomes assessed for up to 2 years before and after eculizumab initiation included percentages and rates per patient per year (PPPY) of exacerbations and crises (the latter defined as intubation/impending intubation), healthcare resource utilization, and rescue therapy administration. Results A total of 119 patients diagnosed with MG were enrolled in the study; 92 patients had ≥ 3 months of data both before and during eculizumab therapy and were included in the analyses. The mean rate of MG exacerbations decreased from 0.385 PPPY before eculizumab initiation to 0.152 PPPY during eculizumab treatment (p = 0.0034); the mean rate of MG crises decreased from 0.411 to 0.056 PPPY (p = 0.0018). Rates of healthcare resource utilization and rescue therapy use also decreased significantly during eculizumab treatment. Conclusions This retrospective chart review analysis provides evidence for a beneficial impact of eculizumab treatment on the incidence of MG exacerbations and crises and associated healthcare resource utilization in clinical practice, and on rescue therapy use. These data further support the therapeutic benefits of eculizumab in patients with MG.